Makna Interaksi Simbolik Pareresan di Sukasari Kaler Argapura Majalengka - Teddy Maulana H. S; Titih Nurhaipah (JIKA (Jurnal Ilmu Komunikasi Andalan), 2022)
The concept of event development has undergone very rapid changes following the times, the forms of activity invitations distributed personally from house to house using invitation paper have been replaced with photos or videos sent using social media. Pareresan is a thanksgiving ceremony for an area that only involves local residents with the usual concept of simple activities, namely gathering local residents to sit together, pray to the Creator, and be grateful for the harvest that has been obtained. There are many symbols that are present in the pareresan event, such as the slaughter of a goat which is then taken some parts of the goat's body to be carried during the prayer reading process by the kuncen, in addition to the hanging of the thigh part of the goat on a tree in the middle of a collection of tombs. sacred, which in this case is a form that the community has been grateful to the Creator by buying a goat from the second harvest in the rainy season. All objects and items that are present in the paresan have meanings that continue to change along with changing times.